Associative Characteristics of the Proverb (Texas Journal of Philology, Culture and History, 2022)
In the article it is the proverb, as the genre of the discourse: we evaluate the criteria to characterize the status of the genre of the discourse of the proverb; these criteria are clarified by noting the prototypical defining characteristics of the proverbial genre; the proverbial construction and the figures of style that present the theory of the actualization of proverbs are explained